Dermatology in COVID-19 Pandemic: A review of manifestation, prevention, and treatment of personal protective equipment adverse skin reactions - I Gusti Ayu Nitya Indira; I Made Sutha Saskara (Bali Dermatology Venereology and Aesthetic Journal, 2020)
COVID-19 poses a new challenge to healthcare workers with a new standard of care and managing COVID-19 patients. Healthcare workers must adhere to stricter hand hygiene, and the new personal protective equipment (PPE) protocol brings forth new problems for healthcare workers. Skin problems have become the most common and preventable adverse effects of the daily and prolonged use of PPE. This could inadvertently cause protocol breaches, such as mask touching, scratching, or off-protocol PPE adjustment. Damage in the skin could also cause discomfort, and skin exposure may serve as a new port of entry for a secondary infection. This study reviewed adverse effects, prevention, and therapy of skin problems related to COVID-19 PPE use.